Vitamin D and Premenstrual Syndrome in Healthy Women with Regular Cycles (P18-056-19). (13th June 2019) - Alkhalaf, Zeina; Kim, Keewan; Purdue-Smithe, Alexandra; Radoc, Jeannie; Freeman, Joshua; Yisahak, Samrawit; Kuhr, Dan; Pollack, Anna; Silver, Robert; Sjaarda, Lindsey; Perkins, Neil; Schisterman, Enrique; et al.
Abstract: Objectives: Vitamin D levels have been associated with premenstrual syndrome (PMS) and symptom severity, but data are mixed. Our aim was to assess the relationship between serum vitamin D and PMS in women with regular menstrual cycles. Methods: We looked at vitamin D and PMS using two cohorts of healthy women with regular cycles. BioCycle followed 76 women, for up to 2 menstrual cycles prospectively and EAGeR followed 1191 women with 1–2 prior pregnancy losses. 25(OH)D was measured in serum at baseline in both cohorts, with PMS assessed via questionnaire evaluating the presence and severity of 14 psychological and physical menstrual symptoms the week before and after menses. EAGeR assessed symptoms over the past year, and BioCycle assessed symptoms prospectively over the next cycle. We used status and PMS associations adjusting for age, BMI, race, smoking, income, physical activity, and season of blood draw. Results: 54% and 47% of women had sufficient 25(OH)D (≥30 ng/mL) and 33% and 40% exhibited PMS in BioCycle and EAGeR, respectively. Vitamin D status was not associated with risk of PMS in either cohort (BioCycle: D insufficiency was associated with risk of breast fullness/tenderness (RR 1.27, 95% CI 1.03, 1.55) and generalized aches and pains (RR 1.33, 95% CI 1.01, 1.78), compared to women with vitamin D sufficiency. Similar associations were observed in BioCycle though confidence intervals were wide. No associations were observed between vitamin D status and psychological symptoms. Conclusions: Among women with regular menses, 25(OH)D was not associated with PMS, though it may be associated with individual symptoms. Additional studies are needed to understand these relationships in women with irregular menstrual. Funding Sources: Intramural Research Program, Division of Population Health Research, NICHD. NIH Medical Research Scholars Program. Doris Duke Charitable Foundation.